Understanding and predicting effects of supplemental viscous damping on seismic response of asymmetric one storey systems. - Lin, Wen-Hsiung (Earthquake engineering & structural dynamics.)
Supplemental damping could mitigate the earthquake induced damage in buildings with asymmetric plan, known to be more vulnerable to damage than comparable symmetric plan buildings. This investigation aims to improve the understanding of how and why planwise distribution of fluid viscous dampers (FVDs) influences the response of linearly elastic, one-storey, asymmetric plan systems. Starting with vibration mode shapes, we predict this influence on the modal damping ratios and in turn on the individual modal responses and the total response. These predictions are confirmed by the computed responses, which demonstrated that the reduction in earthquake response of the system achieved by supplemental damping is strongly influenced by its planwise distribution, which is characterized by four parameters. Identified are asymmetric distributions of supplemental damping that are more effective in reducing the response compared to symmetric distribution. The percentage reduction achieved by a judiciously selected asymmetric distribution can be twice or even larger compared to symmetric distribution.